Not (Entirely) Guilty: The Role of Co-offenders in Diffusing Responsibility for Crime. (July 2022) - Rowan, Zachary R.; Kan, Emily; Frick, Paul J.; Cauffman, Elizabeth
Objectives: Test the diffusion of responsibility hypothesis by examining associations between the presence, number, and role of co-offenders and adolescents' perceived responsibility for criminal behavior. Methods: The study uses data from the Crossroads Study, a longitudinal study of 1, 216 male adolescents who were arrested for the first time. A series of generalized ordered logistic regressions assess how different features of the group context are linked to adolescent offending. Models first examine the relationship between the presence of a co-offender and adolescents' perceptions of responsibility for their crime, followed by co-offending specific models examining the impact of the number of co-offenders and role in the co-offense. Results: Adolescents' perceptions of responsibility for criminal behavior decrease when they co-offend, as the size of the group increases, and when crime is not solely their idea. Conclusions: The study's findings are consistent with the diffusion of responsibility hypothesis, which highlights an important psychological experience tied to the group context. The findings contribute to our understanding of adolescent risky decision-making and shed insight into how the group context may facilitate criminal behavior.